2017
DOI: 10.1021/acsami.6b15601
|View full text |Cite
|
Sign up to set email alerts
|

Structure Evolution and Thermoelectric Properties of Carbonized Polydopamine Thin Films

Abstract: Carbonization of nature-inspired polydopamine can yield thin films with high electrical conductivity. Understanding of the structure of carbonized PDA (cPDA) is therefore highly desired. In this study, neutron diffraction, Raman spectroscopy, and other techniques indicate that cPDA samples are mainly amorphous with some short-range ordering and graphite-like structure that emerges with increasing heat treatment temperature. The electrical conductivity and the Seebeck coefficient show different trends with heat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(55 citation statements)
references
References 31 publications
2
46
0
Order By: Relevance
“…Raman spectroscopy was performed to study the structure and electronic properties of the C-PDA nanosheet ( Figure 3a). The two peaks, one at approximately 1380 cm −1 and the other at 1590 cm −1 , were assigned to the D (disordered carbon) and G bands (graphitic carbon), respectively [38,39,48]. It is worthwhile to note that the intensity ratio of the D and G bands, ID/IG, in the PDA film was 0.69, which is significantly low.…”
Section: Raman and Xpsmentioning
confidence: 92%
See 1 more Smart Citation
“…Raman spectroscopy was performed to study the structure and electronic properties of the C-PDA nanosheet ( Figure 3a). The two peaks, one at approximately 1380 cm −1 and the other at 1590 cm −1 , were assigned to the D (disordered carbon) and G bands (graphitic carbon), respectively [38,39,48]. It is worthwhile to note that the intensity ratio of the D and G bands, ID/IG, in the PDA film was 0.69, which is significantly low.…”
Section: Raman and Xpsmentioning
confidence: 92%
“…Because of the complexity of the oxidative self-polymerization of dopamine, the chemical disorder model has been preferentially used in recent studies to describe PDA [39,46,47]. However, after calcination, the C-PDA has been proposed as nitrogen-rich carbon nanosheets [40,48] using the semiconductor model. In addition, the C-PDA film can be easily transferred to arbitrary substrates (e.g., Si wafer) by employing polymethylmethacrylate (PMMA), thus presenting a significant benefit over CVD-graphene.…”
mentioning
confidence: 99%
“…The PDA/PET fabrics show a similar XRD pattern, indicating that the PDA coating has little influence on the crystalline structure of PET fabrics (Figure 8b). This is mainly due to the amorphous structure of PDA formed on the surface of PET fabrics during the self-polymerization process [29]. Apart from the peaks of PET fabrics, the signals of Ag are observed in the diffraction pattern of the Ag/PDA/PET fabrics as shown in Figure 8c.…”
Section: Xrd Patternmentioning
confidence: 93%
“…Previously, it was found that the graphitization of the PDA gives rise to molecular reorganization through additional covalent conjugations between PDA building blocks, culminating eventually in increased crystallinity 26,29 . To closely examine this in PDA and LAPDA films, matrix-assisted laser desorption/ionization time of flight (MALDI-TOF) mass spectrometry was employed.…”
Section: Shown Inmentioning
confidence: 99%